THE EFFECTS OF COOPERATIVE LEARNING MODEL GROUP INVESTIGATION AND MOTIVATION TOWARD PHYSICS LEARNING RESULTS MAN TANJUNGBALAI - Amalia Febri Aristi (Universitas Negeri Medan, 2014)
This study aimed to determine: (1) Is there a difference in student's learning outcomes with the application of learning models Investigation Group and Direct Instruction teaching model. (2) Is there a difference in students' motivation with the application of learning models Investigation Group and Direct Instruction teaching model, (3) Is there an interaction between learning models Investigation Group and Direct Instruction to improve students' motivation in learning outcomes Physics. This research is a quasi experimental. The study population was a student of class XII Tanjung Balai MAN. Random sample selection is done by randomizing the class. The instrument used consisted of: (1) achievement test (2) students' motivation questionnaire. The tests are used to obtain the data is shaped essay. The data in this study were analyzed using ANOVA analysis of two paths. The results showed that: (1) there were differences in learning outcomes between students who used the physics model of Group Investigation learning compared with students who used the Direct Instruction teaching model. (2) There was a difference in student's learning outcomes that had a low learning motivation and high motivation to learn both in the classroom and in the classroom Investigation Group Direct Instruction. (3) There was interaction between learning models Instruction Direct Group Investigation and motivation to learn in improving learning outcomes Physics.